The block book - Hirsch, Elisabeth S. (Washington, D.C : National association for the education, 1996)
Expanded and updated, this classic book helps teachers discover exciting possibilities for block play. It details the rich contributions of blocks to creative and dramatic play as well as to science, maths, social studies, and other learning domains. It also includes practical tips for equipping and organising the block area, plus a chapter on large blocks
Includes bibliographical reference and index.
Keywords: Block building (Children's activity).